Impact of the COVID-19 Pandemic on Obstetricians/Gynecologists - Kirsten A. Riggan, MA, MS (Elsevier, 2021)
Objective: To assess the impact of the coronavirus disease 2019 (COVID-19) pandemic on obstetricians/gynecologists (OB/GYNs). Participants and Methods: A 49-item survey was distributed to OB/GYNs through the websites and electronic mailing lists of professional OB/GYN organizations. The survey was open from June 22, 2020, through November 22, 2020. Of the 122 initiated surveys, 89 were completed (73.0% completion rate); 72 respondents answered at least one open-ended question and were included for qualitative analysis. Results: Respondents reported policy changes, limited personal protective equipment availability, patient compliance with safety protocols and personal protective equipment use, staff shortages, and concerns about COVID-19 exposure as primary stressors related to the pandemic. Respondents felt that the pandemic had a negative professional impact on their relationships with patients and colleagues. Workplace and pandemic stressors resulted in feelings of anxiety and frustration; physical effects were also reported. Some respondents indicated that they were considering early retirement or leaving the profession as a result of the pandemic, which suggests that OB/GYNs may be at increased risk for burnout. Conclusion: The COVID-19 pandemic will have important long-term effects on OB/GYN well-being and workforce retention. Proactive support for OB/GYNs is needed to combat burnout and counteract workforce attrition. Implementing peer support programs that promote healthy emotional processing following adverse events may mitigate these feelings and reduce OB/GYN burnout.